CHILDFREE BY CHOICE : MENJELAJAHI MOTIVASI ,TANTANGAN,DAN PERSEPSI SOSIAL (Universitas Merdeka Madiun, 2025)
Child free is a choice of a person or couple not to have children or offspring for various reasons, child free itself is certainly chosen with various considerations such as, economic aspects, mental / health, and freedom, now in Indonesia child free has begun to be crowded and hot in the discussion, of course the choice not to have children will reap cons both from his family and his environment, we chose a theme entitled